Disparities in disease presentation in the four screenable cancers according to health insurance status. (September 2016) - Amini, A.; Jones, B.L.; Yeh, N.; Guntupalli, S.R.; Kavanagh, B.D.; Karam, S.D.; Fisher, C.M.
Abstract: Objectives: Current guidelines support the use of screening for early detection in breast, prostate, colorectal and cervical cancer. The purpose of this study was to evaluate whether insurance status predicts for more advanced disease in these four currently screened cancers. Study design: The Surveillance, Epidemiology, and End Results (SEER) database was queried for breast, prostate, colorectal and cervix in patients aged 18–64 years. The database was queried from 2007 to 2011, with 425, 614 patients with known insurance status included. Methods: Multinomial logistic regression was used to evaluate insurance status and cancer presentation. Results: Under multivariate analysis for breast cancer, uninsured patients more often had invasive disease (odds ratio [OR]: 1.55), T- (OR: 2.00), N- (OR: 1.59) stage, and metastatic disease (OR: 3.48), and were more often high-grade (OR: 1.21). For prostate cancer, uninsured patients again presented more commonly with higher T-stage (OR: 1.45), nodal (OR: 2.90) and metastatic (OR: 4.98) disease, in addition to higher prostate-specific antigen (OR: 2.85) and Gleason score (OR: 1.65). Colorectal cancer had similar findings with uninsured individuals presenting with more invasive disease (OR: 1.78), higher T (OR: 1.86), N (OR: 1.22), and M (OR: 1.58) stage, in addition to higher carcinoembryonic antigen levels (OR: 1.66). Similar results were seen for cervical cancer with uninsured having higher T (OR: 2.03), N (OR: 1.21), and M (OR: 1.45) stage. Conclusion: In the four cancers detected by screening exams, those without health insurance present with more advanced disease, with higher stage and grade, and more elevated tumour markers. Highlights: We analyse whether insurance predicts for disease presentation in screened cancers. Breast, colorectal, prostate and cervix were selected. The Surveillance, Epidemiology, and End Results (SEER) database was used. A total of 425, 614 cases were included. Uninsured were more likely to present with advanced disease in screenable cancers.